Perceived threat of Covid-19, resilience and coping strategies as predictors of subjective well-being among emerging adults in Malaysia - Low, Yi Lin; Siew, Yi Hang; Wong, Chin Leong (2021)
The outbreak of COVID-19 was resulted in psychological maladjustment and might affect the Malaysia Well-being Index. Present study was a cross-sectional, descriptive study that aimed to examine the predictive effects of perceived threat of COVID-19, resilience, and coping strategies (task-oriented coping, emotion-oriented coping, avoidance-oriented coping) on SWB among emerging adults in Malaysia. A total of 162 participants was recruited using purposive sampling method by distributing online survey via social media like WhatsApp, WeChat, Instagram. The participants recruited are those emerging adults aged between 18 to 25 years old (M = 22.51). There were more female (N = 111; 68.5%) than male participants in present study (N = 51; 31.5%). The finding revealed that resilience and emotion-oriented coping were a significant predictor of SWB however it does not match with the hypotheses in present study. Perceived threat of COVID-19, task-oriented coping and avoidance-oriented coping not significantly predict SWB.